Identification and gene mapping of rice glutinous mutant r162 - HE Yuzhe; XU Shanbin; CHEN Yanyu; YANG Xue; DUAN Erchao; TENG Xuan; WANG Yihua; DONG Hui; WAN Jianmin (浙江大学学报. 农业与生命科学版, 2024)
Amylose is widely regarded as an important factor affecting the eating quality and appearance quality of rice. It is mainly synthesized by granule-bound starch synthase Ⅰ (GBSSⅠ) encoded by the Waxy (Wx) gene. In this study, the glutinous mutant r162 was obtained from an ethyl methanesulfonate (EMS)-treated population of japonica rice cv. Ningjing 2. Compared with wild type (WT), the grains of this mutant showed a significant decrease in length, width and 1 000-grain mass, presenting a dull, opaque appearance reminiscent of clouds or fog. Scanning electron microscopy analysis of starch morphology revealed that there were some pores in the starch granules of mutant r162. The iodine staining of semi-thin sections indicated that the amyloplast arrangement in the developing endosperm of mutant r162 was similar to that in the WT, but the staining color was lighter. Physicochemical property analysis revealed that the total starch, total protein and total lipid contents of mutant r162 and WT were not significantly different. However, the apparent amylose content significantly decreased, and the gel consistency increased in mutant r162. Besides, the pasting property was also significantly altered, and the breakdown, setback, consistency, and the swelling volume of rice flour in urea of mutant r162 were lower than WT. Through the gene mapping and sequencing, the mutant gene Wx was localized on the short arm of chromosome 6. The first base of the seventh intron 7 (Int7-1) of the Wx gene in the mutant r162 was replaced from guanine (G) to adenine (A), resulting in a deletion of 10 bases in the Wx coding sequence and causing a mistranslation from the 256th amino acid, leading to premature termination of protein translation. Therefore, it was named Wx－r162. Further Western blot analysis revealed a marked decrease in GBSSⅠ protein levels in mutant r162, and enzyme activity assay also showed that the activity of GBSSⅠ in the mutant r162 was significantly lower than that in WT. In summary, the Wx－r162 gene is a novel allelic variant whose mutation causes a decrease in GBSSⅠ activity, resulting in reduced apparent amylose content and an opaque phenotype in grains.